Tuning the magnetic and magnetocaloric properties of austenitic Ni-Mn-(In, Sn) Heuslers. (September 2019) - Cavazzini, G.; Cugini, F.; Gruner, M.E.; Bennati, C.; Righi, L.; Fabbrici, S.; Albertini, F.; Solzi, M.
Abstract: In this work, we highlight the occurrence of different physical mechanisms that independently control the saturation magnetization and the ferro-paramagnetic transition temperature of Ni-Mn-based Heusler compounds, opening new possibilities in mastering the functional properties of this wide class of magnetic materials. We present the magnetic, structural and magnetocaloric features of a complete Ni48 Mn36 In16−x Snx (x = 0–16) series. The observed different trends of the critical temperature and of the saturation magnetization on varying the Sn to In ratio are discussed with the help of first-principles calculations of the electronic structure and magnetic interactions of the compound. Graphical abstract: Unlabelled Image